Actualización del manejo integral terapéutico de la enfermedad renal diabética - Betancourt Vera, Edgar Vicente (Machala : Universidad Técnica de Machala, 2022)
Introduction: Diabetic kidney disease (DKD) is considered a renal complication of great importance, especially long-term of mainly type 2 diabetes mellitus, likewise it is the main condition for the development of chronic kidney disease (CKD) and especially terminal condition, globally. It affects about 40% of patients with DM2 and 30% of patients with DM1. Objective: To identify the new perspectives of the therapeutic approach to diabetic kidney disease, through the analysis of scientific information of evidence-based medicine, for an adequate therapeutic understanding, and to decrease its progression, improving the quality of life of the population. Methodology: The present study is a systematic bibliographic review of different scientific articles from the last 5 years, of evidence-based medicine, from multiple high-impact digital repositories in health (Scopus, Pubmed, Medigraphic, Elsevier, Cochrane) and scientific literature in internal medicine, endocrinology and nephrology. Conclusion: At present there are new specific drugs with a greater tendency to nephroprotection, among the recently appeared hypoglycemic agents with great renal and cardiovascular potential are SGLT2 inhibitors, GLP 1 inhibitors and DPP 4 inhibitors; these pharmacological groups in a single or combined therapy in synergy, have demonstrated an important clinical quality in the renal and cardiovascular profile, improving the quality of life of the diabetic population, and even non-diabetic.
Introducción: La enfermedad renal diabética (ERD) se considera una complicación renal de gran importancia, sobre todo de largo plazo de la diabetes mellitus tipo 2 principalmente, así mismo es la condición principal para el desarrollo de enfermedad renal crónica (ERC) y sobre todo condición terminal, a nivel global. Afecta alrededor del 40% de los pacientes con DM2 y un 30% pacientes con DM1. Objetivo: Identificar las nuevas perspectivas del abordaje terapéutico de la enfermedad renal diabética, mediante el análisis de información científica de medicina basada en evidencia, para la comprensión terapéutica adecuada, y disminuir la progresión de la misma, mejorando la calidad de vida de la población. Metodología: El presente estudio se trata de una revisión sistemática bibliográfica de diferentes artículos científicos de los últimos 5 años, de medicina basada en evidencia, de múltiples repositorios digitales de alto impacto en salud (Scopus, Pubmed, Medigraphic, Elsevier, Cochrane) y literatura científica de medicina interna, endocrinología y nefrología. Conclusión: En la actualidad existen nuevos fármacos específicos y con mayor tendencia a la nefroprotección, entre los hipoglucemiantes recientemente aparecidos y con gran potencial renal y cardiovascular son los inhibidores de SGLT2, los inhibidores de GLP 1 y los inhibidores de DPP 4; estos grupos farmacológicos en una terapéutica sola o combinada en sinergia, han demostrado una calidad clínica importante en el perfil renal y cardiovascular, mejorando la calidad de vida de la población diabética, e incluso no diabética.
Keywords: DIABETES; ENFERMEDAD RENAL DIABEICA; NEFROLOGIA; TERAPEUTICA